2019
DOI: 10.1155/2019/6140360
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of KLF4 Protection against Acute Liver Injury via Inhibition of Apelin Signaling

Abstract: Krüppel-like factor 4 (KLF4) is a key transcription factor that regulates genes involved in the proliferation or differentiation in different tissues. Apelin plays roles in cardiovascular functions, metabolic disease, and homeostatic disorder. However, the biological function of apelin in liver disease is still ongoing. In this study, we investigated the mechanism of KLF4-mediated protection against acute liver injury via the inhibition of the apelin signaling pathway. Mice were intraperitoneally injected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…CCl4 can cause hepatic damage by increasing oxidative stress and the inflammatory response ( Mohi-Ud-Din et al, 2019 ). Many chemicals showed a hepatic protective effect in the CCl4-induced mice model by activating the anti-oxidative pathway and increasing antioxidant synthesis ( Ji et al, 2019 ; Yi R. et al, 2020 ; Lyu et al, 2020 ). A growing number of evidences have revealed that metabolic intermediates are involved in many physical and pathological processes, including the regulation of inflammatory response, oxidative stress, and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CCl4 can cause hepatic damage by increasing oxidative stress and the inflammatory response ( Mohi-Ud-Din et al, 2019 ). Many chemicals showed a hepatic protective effect in the CCl4-induced mice model by activating the anti-oxidative pathway and increasing antioxidant synthesis ( Ji et al, 2019 ; Yi R. et al, 2020 ; Lyu et al, 2020 ). A growing number of evidences have revealed that metabolic intermediates are involved in many physical and pathological processes, including the regulation of inflammatory response, oxidative stress, and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the mechanisms through which miR‐7 regulates IL‐1β production in senescent Kupffer cells, we utilized TargetScan databases ( https://www.targetscan.org/ ) and combined them with existing studies, to identify five potential target genes ATG7 (Guo et al., 2022 ), SIRT1 (Maeso‐Díaz et al., 2018 ), KLF4 (Ji et al., 2019 ), YY1 (Tang et al., 2020 ), and FoxO6 (Kim et al., 2019 ) of miR‐7 that are associated with liver tissue aging (Figure 5a ). We then examined the expression of these potential target genes in Kupffer cells from D‐miR‐7 def mice and found that KLF4 showed the most significant enrichment among the five genes in Kupffer cells (Figure 5b ).…”
Section: Resultsmentioning
confidence: 99%
“…Kruppel-like factor 4 (KLF4) is an important factor that mediates genes participated in cell growth, differentiation, and metastasis. 26,27 Additionally, overexpression of KLF4 has been studied in multiple malignant tumors and has been found to regulate various biological functions, including cell proliferation, survival and metastasis. 11,28,29 We have indicated that KLF4 was a downstream target of miR-7-5p.…”
Section: Discussionmentioning
confidence: 99%